Identification and clinical validation of F3 as a peripheral blood biomarker for neonatal hypoxic-ischemic encephalopathy using dataset-specific bioinformatics analysis - Suxiang Pan; Yanan Peng; Jianqing Hu; Yanping Cai; Yibing Zhang; Bijuan Zheng (Frontiers in Pediatrics, 2026)
Background Neonatal hypoxic-ischemic encephalopathy (HIE) is a major cause of neonatal death and long-term neurological disability. Early recognition of high-risk neonates remains difficult because clinical examination, imaging, electrophysiology, and biochemical tests may be limited by timing, access, or early sensitivity. We aimed to identify and clinically validate a peripheral blood biomarker candidate for HIE. Methods Public transcriptomic datasets related to neonatal HIE or experimental hypoxic-ischemic injury were analyzed as separate biological resources. The human whole-blood dataset served as the primary discovery dataset. Experimental rat cortex datasets were analyzed separately and used only as supportive context after ortholog mapping. Candidate prioritization considered nominal human blood evidence, directionally concordant supportive transcriptomic signals, HIE-related disease-gene annotation, and validation in human peripheral blood mononuclear cells (PBMCs). F3 mRNA was measured by qRT-PCR, and full-length tissue factor (flTF) protein was assessed by immunofluorescence and Western blotting in an independent cohort of neonates with HIE ( n = 40) and non-HIE controls ( n = 30). Results With an exploratory nominal screening threshold, dataset-specific analysis identified F3 as a candidate gene with nominal upregulation in the human whole-blood dataset (log2FC = 6.27, nominal P = 0.041, adjusted P = 0.524). Independent experimental hypoxic-ischemic injury datasets showed directionally concordant supportive signals. In the clinical cohort, PBMC F3 mRNA was higher in neonates with HIE than in non-HIE controls (4.2 ± 0.2 vs. 1.0 ± 0.1, P < 0.0001), with increased flTF protein expression. ROC analysis showed good discrimination in this cohort (AUC, 0.844; 95% CI, 0.735–0.953). Conclusion F3/flTF was prioritized as an exploratory peripheral blood biomarker candidate on the basis of nominal human whole-blood transcriptomic evidence, supportive disease-model data, HIE-related disease-gene annotation, and independent PBMC validation. PBMC F3/flTF may help identify HIE and stratify risk, but larger human blood cohorts, confounder-adjusted analyses, and mechanistic studies are needed before clinical use can be considered.